FUNCTIONAL DISABILITY AND PAIN INTENSITY IN NON-SPECIFIC CHRONIC LOW BACK PAIN IN NURSING WORKERS - Zulamar Aguiar Cargnin; Dulcinéia Ghizoni Schneider; Mara Ambrosina de Oliveira Vargas; Ione Jayce Ceola Schneider (Universidade Federal do Paraná, 2019)
Objective: To determine pain intensity and functional disability in patients with non-specific chronic low back pain.Method: Cross-sectional study with 90 nursing workers of a public hospital conducted between August and October 2017. The Roland Morris Questionnaire and Visual Numerical Scale were used. Bivariate analyzes, Pearson or Spearman correlations and Anova test for comparison of means were performed. Result: Pain intensity was moderate and associated with Body Mass Index and limitation in activities of daily living and reduction of work productivity. Functional disability was low and related to having more than one nursing job and aged 41- 50 years.Conclusion: Low back pain intensity and functional disability were associated with work and individual factors. The identification of these factors may favor the implementation of preventive measures and guide more accurate and specific rehabilitation interventions. The relationship between the intensity of pain and disability was significant, positive and moderate.